The Role of Management, Education and Technology in Human Social Welfare and Relief - Zhang, Bingying (International Journal of Management and Education in Human Development, 2022)
Marx did not construct a systematic welfare ideology but formed a series of viewpoints and discourses on welfare. His basic views on social welfare are that social welfare is based on the development of productive forces, social welfare is essentially fair, social welfare is based on the free and comprehensive development of people as the ultimate ideal, and social welfare is concrete and realistic. Based on this, this article proposes corresponding strategies for the development of social welfare from both education and technology, hoping to promote the better development of human social welfare.